Mekanisme Kerja Obat Antihipertensi Yang Bekerja Pada GPCRs dan Tanaman Yang Berpotensi Sebagai Antihipertensi - Chindiana Khutami (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2023)
Hypertension is the medical term for patients with systolic blood pressure above 140 mmHg and diastolic above 100 mmHg. Hypertension is a complex multifactorial disease that contributes to the main causes of morbidity and mortality in industrialized countries: ischemic heart disease and hypertension, stroke, peripheral atherosclerosis and renal failure. Commonly used antihypertensives are usually associated with many side effects. In the last three decades, many concerted efforts have been made to research local plants with hypotensive and antihypertensive therapeutic value. The hypotensive and antihypertensive effects of some of these medicinal plants have been validated and others have not been proven. G-protein coupled-receptors or GPCRs are targets of drug action, whose signaling is mediated by G-proteins. GPCRs are receptors that reside on the cell surface and have seven transmembrane domains. For example, GPR35 is a target for furosemide and bumetanide. This is especially important in cardiovascular disease secondary to hypertension, where the degree of vessel constriction is partly due to increased levels of agonists such as catecholamines and angiotensin II.